Nurses' Role in the Discharge Planning Implementation on Family Readiness Caring for Patients at Home - Jesy Natalia Ginting; Siti Saidah Nasution; Evi Karota Bukit (GLOBAL HEALTH SCIENCE GROUP, 2024)
One of the important components in the management of patient care in hospitals is the role of nurses in implementing discharge planning, which is a structured process of preparing patients to return to their environment after they get treatment in the hospital. Nurses have a significant role in helping families prepare to care for patients after discharge from psychiatric hospitals. Through evaluation of the patient's condition, coordination with multidisciplinary care teams, patient and family education, and preparation of a detailed discharge plan, nurses can positively influence Family Readiness. Objective: to evaluate the relationship between the role of nurses in implementing discharge planning and family readiness to care for patients at home. Method: The sample used was a purposive sample of 78 implementing nurses working in the inpatient room and the design of this study was cross-sectional. Data was collected through questionnaires as well as statistical correlation Chi-Square was used to analyze it. The validity test for the nurse role questionnaire was 0.629 to 0.777, while the family readiness questionnaire was 0.456 to 0.765. The Cronbach's alpha value for the nurse's role variable was 0.962 and family readiness was 0.967 so the questionnaire was declared reliable. Results: The results showed a relationship between the role of nurses in implementing discharge planning and family readiness to care for patients at home (0.020 < 0.05). Conclusions: Thus, the role of nurses in the discharge planning process plays an important role in improving family readiness in caring for patients at home.